Scanless terahertz time-domain imaging - Zanotto, Luca; Balistreri, Giacomo; Rovere, Andrea; Kwon, O. Pil; Morandotti, Roberto; Piccoli, Riccardo; Razzari, Luca (2023 Conference on Lasers and Electro-Optics, CLEO 2023, 2023)
Through diffraction, we combine a single-pixel imaging approach and a single-shot detection technique to achieve scanless time-domain imaging at terahertz frequencies. We also apply compressive sensing to further reduce the acquisition time.
Keywords: Acquisition time; Compressive sensing; Scanless; Shot detection; Single pixel; Single-shot; Tera Hertz; Terahertz frequencies; Time-domain imaging